An Analysis of State Statutes Regarding the Role of Law Enforcement - Cortright, Carly E. (Criminal justice policy review, 2020)
Police officer roles are typically divided into either crime control or peacekeeping/order maintenance functions. With the prevalence of community-oriented policing (COP), the majority of an officer’s duties are ostensibly more order maintenance in nature, but in the post-Ferguson world, the crime-fighting, warrior cop mentality still holds firm, which is in conflict with the tenets of COP. State statutes dictate the legal role of police officer and prior analyses demonstrated a shift over time toward including more order maintenance tasks following the emergence of COP. This analysis reexamines these statutes to determine if this shift continued. Our findings indicate a counterintuitive reversal in the trend, with more states removing order maintenance and peacekeeping duties from their statutes despite the wide dominance of COP.